Sexually transmitted diseases in homosexual males in Seville, Spain. Issue 4 (August 1991) - Rodriguez-Pichardo, A; Aznar, J; Camacho, F; Borobio, M V; Perea, E J
Abstract : BACKGROUND AND METHODS--The absence of any official statistics on the prevalence of STD in homosexual men in Spain induced us to carry out a prospective study of new homosexual patients who consulted the STD Clinic of the School of Medicine in Seville, between January 1988 and December 1989. The aim of the study was to determine the prevalence of symptomatic and asymptomatic infections in this group of patients. RESULTS--1805 patients were seen during the study period; 318 patients were homosexual of whom 309 agreed to participate in the study. Of the 309 homosexual men, 108 (35%) had symptoms and the remaining 201 (65%) were asymptomatic. In the symptomatic group the diagnoses were: syphilis 28 (25.9%); urethritis 40 (37%) (of these 40, 11 had Neisseria gonorrhoeae, five had Chlamydia trachomatis, five had Ureaplasma urealyticum, one had Herpes simplex virus and in 18 no pathogen was detected); genital herpes seven (6.4%). Eleven (10%) had concomitant infections. The following infections were found in the asymptomatic group: syphilis 23 (11.4%), N gonorrhoeae six (3%), C trachomatis two (1%), Herpes simplex virus one (0.5%). Antibodies against HIV were detected in 30 (9.6%) of the total group. CONCLUSIONS--Sexually transmitted diseases are common amongst homosexual men in Seville and many of these are asymptomatic.